PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN TERHADAP PENYERAPAN ANGGARAN DENGAN KEJELASAN ANGGARAN SEBAGAI VARIABEL MODERASI (Studi Kasus Pada IAIN Ambon) - Jumarny Jumarny (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2019)
This study aimed at determining : the effect of absorption, the effect of budgeting clarity on budget absorption, and the effect of budgeting participation and budget absorption with budget clarity as the moderating variable. The Population in this study amounted to 35 people consisting of the Deanof the Faculty, Deputy Dean of General Administration and Financial Planning, Head of General Academic and student Administration Bereau, Head of Division, Head of Subdivision, Head of Department and General Functional position especially in education fieldsat state Islamic Insitute of Ambon. With Purposive Sampling technique, a sample of 35 people was obtained. Techniques of data analysis used in this study were multiple linear regression analysis and T test to examine the effect of independent variables, moderate variables, and dependent variables. The result of this study showed that : 1) budgeting participation did not affect the budget absorption because the significant value exceeds alpha 5% which is 41,3%. 2) budget clarity affected budget absorption because the significant value is less than alpha 5% which is 0%. 3) budgeting participation affected budget absorption with budget clarity as the moderating variable because the significant value is less than alpha 5% which is 0%. Keyword : Budgeting Participation, Budget Clarity, Budget Absorption.